Mistaken for Mourning: Freud and the Economic Problem of Derrida’s Marxism - Jukić, Tatjana (2009)
Taking up Freud’s positions on economy and mourning where they depend on the contact they organize with masochism and melancholia, my presentation aims at a critical reading of Derrida’s assemblage of mourning and economy in Specters of Marx: the State of the Debt, the Work of Mourning and the New International. Insofar as masochism and melancholia, in Freud, appear to labor as errors of psychoanalysis, yet errors constituent to analyzing economy and mourning, my reading proposes to address this particular assemblage of Freudian error as the state of the debt of Derrida’s Marxism itself, or rather the state of the debt of what in Derrida’s Marxism labors as the promise of philosophy.